Insights into the structure and self-assembly of organic-semiconductor/quantum-dot blends - Toolan, DTW; Weir, MP; Allardice, J; Smith, JA; Jones, RAL (Wiley, 2021)
Controlling the dispersibility of crystalline inorganic quantum dots (QD) within organic-QD nanocomposite films is critical for a wide range of optoelectronic devices. A promising way to control nanoscale structure in these nanocomposites is via the use of appropriate organic ligands on the QD, which help to compatibilize them with the organic host, both electronically and structurally. Here, using combined small-angle X-ray and neutron scattering, the authors demonstrate and quantify the incorporation of such a compatibilizing, electronically active, organic semiconductor ligand species into the native oleic acid ligand envelope of lead sulphide, QDs, and how this ligand loading may be easily controlled. Further more, in situ grazing incidence wide/small angle X-ray scattering demonstrate how QD ligand surface chemistry has a pronounced effect on the self-assembly of the nanocomposite film in terms of both small-molecule crystallization and QD dispersion versus ordering/aggregation. The approach demonstrated here shows the important role which the degree of incorporation of an active ligand, closely related in chemical structure to the host small-molecule organic matrix, plays in both the self-assembly of the QD and small-molecule components and in determining the final optoelectronic properties of the system.